2002
DOI: 10.1161/01.res.0000024412.24491.ca
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxic Induction of the Hypoxia-Inducible Factor Is Mediated via the Adaptor Protein Shc in Endothelial Cells

Abstract: Abstract-Tyrosine kinase cascades may play a role in the hypoxic regulation of hypoxia-inducible factor (HIF)-1. We investigated the role of tyrosine kinase phosphorylation and of the Shc/Ras cascade on hypoxic HIF-1 stabilization. Exposure of human umbilical vein endothelial cells to hypoxia results in HIF protein stabilization as early as 10 minutes, with a maximum at 3 hours, and also in Shc tyrosine phosphorylation, with a maximum at 10 minutes. Key Words: hypoxia Ⅲ hypoxia-inducible factor-1 Ⅲ Shc Ⅲ Ras Ⅲ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
30
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 48 publications
4
30
0
Order By: Relevance
“…Thus, it is possible that the hypoxic effects are mediated by the recruitment of specific signaling relay proteins and nonreceptor tyrosine kinases. For example, the adaptor protein shc, an immediate substrate of tyrosine kinases, may play an important role in linking hypoxic conditions to downstream signaling events, such as induction of hypoxic inducible factor (37). The IC 50 for inhibiting EGFR phosphorylation by PKI 166 is reported to be 10 nM (28), but in our experiment, PKI 166 inhibited PI3K/Akt/ NF-B and MEK/MAPK(Erk) at a micromolar concentration.…”
Section: Discussionmentioning
confidence: 54%
“…Thus, it is possible that the hypoxic effects are mediated by the recruitment of specific signaling relay proteins and nonreceptor tyrosine kinases. For example, the adaptor protein shc, an immediate substrate of tyrosine kinases, may play an important role in linking hypoxic conditions to downstream signaling events, such as induction of hypoxic inducible factor (37). The IC 50 for inhibiting EGFR phosphorylation by PKI 166 is reported to be 10 nM (28), but in our experiment, PKI 166 inhibited PI3K/Akt/ NF-B and MEK/MAPK(Erk) at a micromolar concentration.…”
Section: Discussionmentioning
confidence: 54%
“…HIF-mediated reporter gene activity was shown to be decreased by Morg1 while suppression of Morg1 led to a marked increase of HIF-1 activity. There are also data showing that the adaptor protein Shc which possess two distinct domains that bind phosphotyrosine containing sequences (PTB and SH2) and a cen- tral region that contains critical tyrosine phosphorylation sites (47) and its downstream effectors, Ras and Raf-1, are involved in hypoxia-induced HIF-1 stabilisation in human umbilical vein endothelial cells (48). In these cells overexpression of a dominantnegative Shc mutant resulted in significantly reduced HIF-1α protein levels as compared with control.…”
Section: Discussionmentioning
confidence: 99%
“…Jung et al 4 report that a Shc-Ras signaling pathway regulates endothelial cell migration, probably as a result of HIF-1␣ protein stabilization. Previously, Gu et al 21 reported that Shc and FAK regulated cell migration through two different mechanisms: one is a pathway from Shc through the MAP kinase pathway leading to the stimulation of random cell motility, and the other is from FAK through p130Cas leading to stimulation of directionally persistent cell migration.…”
Section: Cell Migration and Shcmentioning
confidence: 99%
“…Among these pathways, the hypoxia-inducible transcription factor-1 (HIF-1␣) plays an essential role by transactivating the VEGF gene and activating a pattern of gene expression associated with mobilization, migration, and recruitment of endothelial cells and smooth muscle cells to form new blood vessels. [1][2][3] The report by Jung et al 4 in this issue of Circulation Research investigates the signaling pathway responsible for hypoxia-induced HIF-1␣ protein stabilization and concludes that a mechanism involving Src, Shc, Ras, and Raf-1 is critical in endothelial cells.…”
mentioning
confidence: 99%
See 1 more Smart Citation